Anaerobic co-digestion of a lignocellulosic residue with different organic wastes: Relationship between biomethane yield, soluble organic matter and process stability. (October 2021) - Cucina, Mirko; Pezzolla, Daniela; Tacconi, Chiara; Gigliotti, Giovanni
Abstract: The aim of this paper was to deepen the knowledge of anaerobic co-digestion of lignocellulosic residues and evaluate the role of soluble organic matter during co-digestion. Buckwheat milling residue (buckwheat hull) was co-digested with different organic wastes to evaluate the effect of co-digestion on biomethane yield, process stability, and their relationship with soluble organic matter. Results showed that co-digestion increased the biomethane yields of buckwheat hull and the best result was achieved from the co-digestion with slaughterhouse wastes (+254% of cumulative biomethane production). Kinetic analysis showed that fruit wastes and brewery trub affected positively anaerobic digestion of lignocellulosic residues, enhancing biomethane potential (+84% and +166%, respectively) and reducing lag phase duration. A positive correlation was found between the soluble organic matter and the biomethane yields during co-digestion experiments. Nevertheless, co-digestion with fruit wastes was affected by an excessive acidification in the early stage of AD (pH 5.7) caused by the rapid conversion of sugars into volatile fatty acids (7 g L -1 at day 15). Although all the digestates showed high concentrations of plant nutrients (the average content of total N was 7.8% dry weight), they were also characterized by residual phytotoxicity (germination index was always 0.0%). results. Increasing the amount of easy biodegradable organic matter during lignocellulosic residues treatment should be the main goal when selecting co-digestion substrates. Chemical composition of co-digestion substrates should be carefully considered, with particular regard to soluble organic matter, to ensure the optimal development of anaerobic digestion with lignocellulosic residues. Graphical abstract: Image 1 Highlights: Different co-digestion substrates were tested for lignocellulosic residue digestion. Soluble organic matter concentration and composition play a key role in co-digestion. Increased soluble organic matter enhanced biomethane yields. Composition of co-digestion substrates affects process stability. Agroindustrial wastes are ideal codigestion substrates for lignocellulosic residue.